Assessment of the effects of a parental intervention with mothers of children with internalizing problems - Orti, Natália Pinheiro; Bratifish, Miriam; Bolsoni-Silva, Alessandra Turini [UNESP] (My University, 2015)
The present study assesses the effects of a semi-structured intervention held exclusively with mothers and its effects on internalizing problems, social skills of children, and positive and negative parenting practices. The single subject experimental design with three participants was adopted. The three mothers had, in baseline, children diagnosed with internalizing and externalizing problems. The instruments used were CBCL, RE-HSE-P, QRSH-Pais and PHQ-9, they were performed in baseline, pre-test, post-test, and follow-up assessments. The intervention held is characterized as semi-structured for it promotes the development of parental practices that are considered positive by the literature on behavior problems, however, contingently to the difficulties and demands of each case. The number of sessions performed for each case was 14, 15 and 17, which lasted about two hours each. The data were analyzed according to the instruments' norms and under the perspective of each singular case. The results found include remission of internalizing problems, increase in frequency of the children's social skills, increase in frequency of positive parental practices, and decrease in variability of negative parental practices. All the improvements were maintained on the six months follow-up, with the exception of variability on the negative parental practices of one client. Results are discussed in a context of mental health promotion and indicate the need for strategies to prevent internalizing problems in children.
Keywords: Internalizing problems; Parental practices; Parent training; Single case design